Lifespan and reproductive dynamics of the commercially important sea bob shrimp Xiphopenaeus kroyeri (Penaeoidea): synthesis of a 5-year study - Castilho, Antonio L. [UNESP]; Bauer, Raymond T.; Freire, Fúlvio A. M.; Fransozo, Vivian Fransozo; Costa, Rogério C. [UNESP]; Grabowski, Raphael C. [UNESP]; Fransozo, Adilson [UNESP] (Oxford University Press (OUP), 2015)
Population parameters of the shrimp Xiphopenaeus kroyeri (Heller, 1862) (sex ratio, length-frequency distributions (carapace length, CL), growth, lifespan, size of sexual maturity, spawning and recruitment) were analyzed in a long-term study from January 1998 through June 2003. The data on these parameters were collected and analyzed to test the hypothesis that the main period of juvenile recruitment in the bay coincides with the period of fishery closures currently designated by the Brazilian Institute of Environment and Renewable Natural Resources. Monthly collections were conducted along the southeastern Brazilian coast, using a shrimp fishing boat with “double-rig” nets sampling at stations up to 40 m depth. Sex ratios were female-biased only in zones with high reproductive activity such as in stations deeper than 15 m (χ2 test, p<0.05). The mean size of males and females was 15.3 ± 3.1 mm CL and 16.2 ± 4.7 mm CL, respectively, with size at sexual maturity estimates (CL50) of 14.8 mm for males and 15.5 mm for females. Mean growth curves provided estimates of CL∞ = 29.31 mm, k = 0.009/day, t0=−0.25 and CL∞ = 35.33 mm, k = 0.006/day, t0=−0.23 for males and females, respectively, and average lifespans of 1.35 for males and 2.12 years for females. Recruitment and abundances of reproductive females were highly correlated with the environmental factors such as higher water temperature and finer-grained bottom sediment (canonical correlation, r=0.63, p<0.001). The reproductive peaks in February-April 1998, March-May 1999 and February-May 2002 were followed by recruitment peaks in May-July 1998, July-September 1999 and April-June 2002, respectively. Thus, the proposed period of fisheries closure (March to May) does not coincide with the main recruitment periods observed for X. kroyeri.
Keywords: Population dynamics; Recruitment; Fisheries biology; Penaeoidea; Reproductive pattern